Strengthening Methods of Room and Cryogenic Temperatures Mechanical Properties of Fe45Mn15Cr15Ni25 High Entropy Alloy - Dan LIU; Junwei QIAO (Taiyuan Ligong Daxue xuebao, 2021)
In order to develop cobalt-free low-cost high entropy alloys(HEAs), non equiatomic ratio Fe45Mn15Cr15Ni25 high entropy alloy was designed and prepared through thermodynamic parameters and phase diagram calculation, cold rolling and annealing processes, and the mechanical properties at ambient (293 K) and cryogenic temperatures (77 K) were analyzed. The results show that the single-phase face-centered cubic (FCC) high entropy alloy has excellent mechanical properties at room temperature and cryogenic temperatures. In particular, at 77 K, the cold-rolled alloy achieves the comprehensive properties of yield strength 1 020 MPa, tensile strength 1 180 MPa, and elongation 20%. For recrystallized alloy at ambient temperature, the intrinsic lattice stress is 86 MPa, the Hall-Petch coefficient is 534 MPa·μm1/2, and the grain boundary strengthening is obvious. For the cold-rolled alloy at cryogenic temperature, the strain hardening ability is restored, the dislocation strengthening is significant, and the strength and ductility are improved simultaneously.